Design and Construction of Fish Seed Grading Tools as an Early Introduction To Entrepreneurship at SMKN 1 Meureubo, West Aceh - Citra Dina Febrina; Mahendra Mahendra (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
This research-based community service aims to develop several research results from research teams and other researchers who are in the same field of science, namely the field of aquaculture or aquaculture, to overcome the problems faced by partners. This service was motivated by the partner's problem at SMK Negeri 1 Meureubo, West Aceh, namely that the results of raising catfish were less than optimal because catfish have cannibalistic characteristics so that in making a catfish grading tool, partners were able to increase the results of cultivating catfish. This is also supported by the absence of manufacturers making catfish grading equipment in West Aceh in particular and Aceh in general. Apart from that, making this grading bucket can also provide additional income for students at SMKN 1 Meureubo school through early introduction to entrepreneurship for students at school as well as to develop an entrepreneurial spirit and improve students' skills in making useful products in the field of Aquaculture. The method used in this service is through a direct approach and active participation of students in making catfish seed grading buckets. Activities include outreach in the form of lectures and discussions, practice of making grading buckets directly at school as well as mentoring the service team in developing the entrepreneurial spirit of students at partner schools. The output of the service that has been carried out is a draft article to be published in a national journal. Output also produces products that can be marketed online and offline.